Implementing Risk Adjusted Capitation Payments with Health Care Reforms in Hung - Nagy, Balázs; Brandtmüller, Ágnes (Competitio, 2008)
Since the late nineties Hungarian governments have been considering the introduction of new health care arrangements by establishing organizations with devolved responsibilities for the management of health care. These organizations are typically financed through a weighted (risk adjusted) capitation system which is regarded as an adequate and optimal tool for resource allocation purposes. Through capitation one needs to handle large inequities in the Hungarian health care system and keep an eye on the incentives for efficiency. For the capitation formula a relatively broad choice of risk adjusters are available in the form of pharmacy- and diagnosis-based patient level utilization data (health-based adjusters) and area level socio-economic data (non health-based adjusters). The instant application of health-based adjusters has limitations because they reflect a distorted provider structure and offer perverse incentives; therefore a gradual shift from using non health-based adjusters to health-based adjusters is preferred. The early phase of the capitation system also implies a strong presence of risk sharing arrangements and other complementary policies. Given that promoting efficiency and equity are to be pursued, the capitation approach outlined in this paper should serve as a guide to future Hungarian health care system reforms. Journal of Economic Literature (JEL) code: I28, G28, G32, H51